The cannabinoid‐1 receptor inverse agonist taranabant reduces abdominal pain and increases intestinal transit in mice. Issue 8 (21st May 2013) - Fichna, J.; Sibaev, A.; Sałaga, M.; Sobczak, M.; Storr, M.
Abstract Background Constipation‐predominant irritable bowel syndrome (IBS‐C) is a common functional gastrointestinal (GI) disorder with abdominal pain and decreased motility. Current treatments of IBS‐C are insufficient. The aim of this study was to evaluate the potential application of taranabant, a cannabinoid type 1 (CB1) inverse agonist using mouse models mimicking the symptoms of IBS‐C. Methods Changes in intestinal contractile activity were studied in vitro, using isolated mouse ileum and colon and intracellular recordings. In vivo, whole gastrointestinal transit (WGT) and fecal pellet output (FPO) were measured under standard conditions and with pharmacologically delayed GI transit. The antinociceptive effect was evaluated in mustard oil‐ and acetic acid‐induced models of visceral pain. Forced swimming and tail suspension tests were performed and locomotor activity was measured to evaluate potential central side effects. Key Results In vitro, taranabant (10−10–10−7 mol L−1) increased contractile responses in mouse ileum and blocked the effect of the CB agonist WIN 55, 212‐2. Taranabant had no effect on the amplitude of electrical field stimulation (EFS)‐evoked junction potentials. In vivo, taranabant (0.1–3 mg kg−1, i.p. and 3 mg kg−1, p.o.) increased WGT and FPO in mice and reversed experimental constipation. The effect of taranabant was absent in CB1−/− mice. Taranabant significantly decreased the number of pain‐related behaviors in animal models. At the doses tested, taranabant did not display mood‐related adverse side effects typical for CB1 receptor inverse agonists. Conclusions & Inferences Taranabant improved symptoms related to slow GI motility and abdominal pain and may become an attractive template in the development of novel therapeutics targeting IBS‐C.